2022
DOI: 10.3390/met12111881
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ta Doping on the Microstructure and Thermoelectric Properties of Bi2O2Se

Abstract: In this study, Bi2−xTaxO2Se (x = 0, 0.02, 0.04, 0.06, and 0.08) ceramics were prepared using a synthesis method combining high-energy ball milling and cold pressing. Furthermore, the effects of tantalum (Ta) doping on the microstructure and thermoelectric properties of Bi2O2Se were systematically investigated. The results indicate that Ta doping effectively improves the carrier concentration and mobility, thus increasing the electrical conductivity from 8.75 S cm−1 to 39.03 S cm−1 at 323 K. Consequently, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…Substituting the parent compound with a suitable element can lead to a better property. Transition metals (Nb, Ta), [142,143] post-transition metals (Sn), [144] Lanthenides (La, Ce), [145,146] Metalloids (Sb) [147] doping has been substituted at Bi-site that renders high carrier concentration and mobility, and it increases the electrical conductivity and reduce the lattice thermal conductivity, which further improves the thermoelectric performance. Reactive non-metals, such as I and Cl are also doped at the Se-site for increasing carrier concentration to enhance the thermoelectric performance of Bi 2 O 2 Se.…”
Section: Dopingmentioning
confidence: 99%
“…Substituting the parent compound with a suitable element can lead to a better property. Transition metals (Nb, Ta), [142,143] post-transition metals (Sn), [144] Lanthenides (La, Ce), [145,146] Metalloids (Sb) [147] doping has been substituted at Bi-site that renders high carrier concentration and mobility, and it increases the electrical conductivity and reduce the lattice thermal conductivity, which further improves the thermoelectric performance. Reactive non-metals, such as I and Cl are also doped at the Se-site for increasing carrier concentration to enhance the thermoelectric performance of Bi 2 O 2 Se.…”
Section: Dopingmentioning
confidence: 99%
“…Recently, the n-type Bi 2 O 2 Se TE materials have attracted researchers' attention because of their high Seebeck coefficient and low thermal conductivity [21]. Jiang et al [22] reported that the Ta doping of Bi 2 O 2 Se can improve the zT value from 0.11 to 0.18 at ~773 K. Pan et al [23] reported that the sulfur substitution of oxygen in Bi 2 O 2 Se can improve the electrical conductivity and then promote the zT value from 0.1 (original) to 0.29 at ~773 K. Liu et al [24] investigated the improvement of zT value by Ge doping. A maximum zT value of 0.3 at ~823 K was found in this study.…”
Section: Introduction mentioning
confidence: 99%
“…This can be calculated using the equation ZT = S 2 σT/κ. In this equation, S, σ, T, and κ represent the Seebeck coefficient, electrical conductivity, absolute temperature, and thermal conductivity, respectively [3][4][5]. Nonetheless, the interdependence of S, σ, and κ presents a challenge in simultaneously optimizing multiple parameters and enhancing thermoelectric performance.…”
Section: Introductionmentioning
confidence: 99%